Relationship between Accessory Renal Artery and Clinical Characteristics of Middle-Aged Patients with Primary Hypertension - Kai Kang; Yeshuo Ma; Chongfu Jia; Yunpeng Cheng; Yingchao Yang; Lixin Wang; Yinong Jiang; Yan Lu (International Journal of Hypertension)
Objectives. The association between accessory renal artery (ARA) and hypertension remains not fully understood. We observed the association between ARA and clinical characteristics among middle-aged patients with primary hypertension. Methods. One hundred and sixty-two middle-aged (mean 39.82 ± 10.25 years, 58.0% male) patients with primary hypertension were enrolled, and patients underwent Computed Tomography Angiography (CTA) of renal arteries, ambulatory blood pressure monitor (ABPM), echocardiography, physical examination, and routine blood chemistry examinations. According to the CTA results, patients were divided into a non-ARA (n = 108) and ARA (n = 54) group. Direct renin concentration (DRC), plasma aldosterone concentration (PAC), ABPM, echocardiography, creatinine, and glomerular filtration rate were compared between the two groups. Results. DRC (mU/L) (11.21 (5.34, 20.87) vs. 18.24 (10.32, 33.59), P=0.002) was significantly higher in the ARA group than in the non-ARA group. However, PAC (ng/dL) (98.30 (67.30, 134.00) vs. 116.50 (78.80, 137.25), P=0.103) was similar between these two groups. ABPM (mmHg) results showed that daytime (146.75 ± 17.04/95.86 ± 11.39 vs. 155.50 ± 14.76/100.48 ± 10.69, P<0.05), night time (133.44 ± 17.50/85.28 ± 12.80 vs. 139.81 ± 14.64/89.83 ± 11.21, P<0.05), and 24 h blood pressure (143.95 ± 15.99/93.90 ± 11.78 vs. 152.07 ± 13.85/98.11 ± 10.36, P<0.05) were significantly higher in the ARA group than in the non-ARA group. Accordingly, echocardiographic-derived posterior left ventricular wall thickness value was higher in the ARA group than in the non-ARA group. Conclusion. ARA is related to higher blood pressure and higher direct renin concentration in middle-aged patients with primary hypertension, and these patients deserve stricter blood pressure control. Our results provide important evidence for that ARA is a cause of hypertension and target organs damages.